Positive and negative politeness strategies used by english major students of International Islamic University Malaysia (IIUM) in communicating through Whatsapp - Wardah Ismail
The purpose of this research is to identify the type of positive and negative politeness strategies used by Malaysian IIUM BENL students in WhatsApp conversations since the lack of politeness in society has begun to generally increase irrespective of the interlocutors in the communication process. Positive and negative politeness strategies refer to strategies which are performed when people interact with others regardless of the social distance they share. This research is based on Brown and Levinson's (1987) theory of politeness. As a qualitative research, this study was conducted in several steps. It involved collecting 50 WhatsApp conversations from Malaysian IIUM BENL students between April 1st, 2018 to May 31st, 2018. The frequency and percentage of positive and negative politeness strategies were counted and the type of positive and negative politeness strategies used by Malaysian IIUM BENL students in these WhatsApp conversations were identified. The major finding of the study indicates that students demonstrated more positive politeness strategies when sending WhatsApp message to those they are close to like family and friends but used more negative politeness strategies when communicating with strangers.